Odpowiedź :
(-1½)(do potęgi 7) x (-1½) : (-1½)(do potęgi 6)=(-1½)(do potęgi 2)
(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11) =
=(-1½)(do potęgi 2)
(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11) =
=(-1½)(do potęgi 2)
(-1½)(do potęgi 7) x (-1½) : (-1½)(do potęgi 6)=(-1½)⁸: (-1½)(do potęgi 6)
(-1½)²=9/4=2¼
(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11)=(-1½)¹³: (1½) (do potęgi 11)=(-1½)²=9/4=2¼
(-1½)²=9/4=2¼
(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11)=(-1½)¹³: (1½) (do potęgi 11)=(-1½)²=9/4=2¼
(-1½)⁷ x (-1½) : (-1½)⁶ = (-1½)⁸:(-1½)⁶=(-1½)²=2¼
(-1½)⁵ x (-1½)⁸ : (1½)¹¹=(-1½)¹³:(-1½)¹¹=(-1½)²=2¼
(-1½)⁵ x (-1½)⁸ : (1½)¹¹=(-1½)¹³:(-1½)¹¹=(-1½)²=2¼